Time gap effect on bond strength of 3D-printed concrete. Issue 1 (2nd January 2019) - Tay, Yi Wei Daniel; Ting, Guan Heng Andrew; Qian, Ye; Panda, Biranchi; He, Lewei; Tan, Ming Jen
ABSTRACT: An advancing technology that combines the concrete extrusion with a motion control to create structures with complex geometrical shapes without the need for formwork is known as 3D concrete printing. Since this technique prints layer by layer, the time taken to reach the same position in the subsequent layer is important as it will create an anisotropic property that has a weaker tensile strength at the bond interface of the two printed filaments. Through rheological measurement, which reveals the material deformation and flow behaviour, it is possible to examine the material structural build-up due to time-gap effect by measuring at different time delay. This paper focuses on investigating the time-gap effect on the printed filament with rheological and observation at macroscopic-scale to understand the material behaviour of the initial and subsequent printed layer during its fresh phase. Rheological experiment findings reveal that the tensile strength of the printed specimen is correlated to the material modulus at the initial layer.